The to-and-for of words. Poetry and myth in Vargas Vicuña's work - Larrú Salazar, Manuel (2014)
Many critics have acknowledged the stylistic and technical skills in Eleodoro Vargas Vicuña’s narrative, such as the orality of his characters, narrative fragmentation and polyphonic voices that describes his plot. There have been suggestions that the Indigenism of Vargas Vicuña renewed the pro-Indian narrative universe, but there are few concerns about the links of his story with his poetic production. Our research aims to establish which type of narrator rules his work. We will also show how his characters start showing through a particular language in order to reveal a vision of reality strongly linked to that of his poetic work, a transculturalized and mixed-raced discursive formation, but whose roots are related to his first reference: the mythical Andean perspective.